Mobilizacija i razvoj zajednica : akcijsko istraživanje u Hrvatskoj - Stubbs, Paul; Kregar Orešković, Klaudija; Bagić, Aida; Bratković, Daniela; Bubanović Devčić, Helga; Ćorić, Gordana; Papa, Jasmina; Miošić-Lisjak, Nives; Škrabalo, Marina (MAP Savjetovanja, 2006)
Summary